Development of Non-Invasive Blood Glucose Level Monitoring System using Phone as a Patient Data Storage - Riska Ekawita; Ahmad Azmi Nasution; Elfi Yuliza; Nursakinah Suardi; Suwarsono Suwarsono (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Glucose levels that accumulate in the blood can cause other organ disorders and even cause death. To prevent such occurrence, continuous and regular glucose measuring and monitoring is required for diabetes mellitus (DM) patients. Glucose measurement for DM patients are generally performed several times a day, so be required easy, harmless method of measuring the DM patients, and monitoring data are well recorded. Thus in this research, an android non-invasive glucose level system with wireless communication and automatic data storage on the phones memory was developed. The study was begun with the built of electronic and software systems as the central part of the measuring system. The electronic section consists of laser and light sensors that respond to a change in blood glucose (BG) levels, the microcontroller that controlled all of the measuring processes, and Bluetooth modules as transceiver on data communication of the android. The software section is built using an App Inventor developed by the Massachusetts Institute of Technology (MIT) to display and store data measurement on the mobile phone. The calibration process of light sensors is done with the standard tool and at last, the wireless communication systems testing and BG levels measurement. The result shows that 94 mg/dl of BG levels by standard tools equals 2.86 volts of voltage measured by the design system. The higher the BG level, the lower the voltage be. Increase the BG level causes the resistance between the transmitter and the receiver to raise and the voltage becomes low.